(untitled) (The International Journal of Educational Sciences and Arts, 2026)
The current study aimed to identify the training needs of Arabic language teachers in light of sustainable professional development; to achieve the study’s objective, a mixed approach with a sequential explanatory design was used, relying on two tools: a questionnaire and an interview. The study sample consisted of a simple random sample of (95) Arabic language teachers. The interview was applied purposively to a sample of (6) teachers from the study sample. The results showed that the cognitive and skills training needs were very high, with the needs related to modern technologies, knowledge production, and critical thinking topping the list. In addition, there was a need to know the most important educational problems facing the teacher in the field. The results also revealed the existence of obstacles to a high degree, the most prominent of which are: the large number of administrative burdens, the lack of time, and the gap between training and reality. The analysis of the interviews showed a strong positive trend and awareness of the importance of professional sustainability to keep pace with the digital generation. However, this trend clashes with the reality of implementation, as it lacks institutional support and material and moral incentives. In addition, there is a gap in the timing and content of some training programs. The study recommended the necessity of designing training programs that stem from the actual needs of teachers, in addition to allocating official hours within the school timetable that allow for the professional development of the teacher.